Legal and practical issues raised by the movement of people across the Mediterranean - Goodwin-Gill, G (Refugee Studies Centre, University of Oxford, 2016)
The movement of people is a phenomenon we must learn to live with and to manage as best we can in the interests of all. Among other matters, this will require states dealing with each other on a basis of equity and equality, rather than outmoded and unrealistic expectations of sovereign entitlement.